2020
DOI: 10.1128/aac.01693-20
|View full text |Cite
|
Sign up to set email alerts
|

Azole and Amphotericin B MIC Values against Aspergillus fumigatus : High Agreement between Spectrophotometric and Visual Readings Using the EUCAST EDef 9.3.2 Procedure

Abstract: The EUCAST 9.3.2 procedure recommends visual readings of azole and amphotericin B MICs against Aspergillus spp. Visual determination of MICs may be challenging. In this work, we aim to obtain and compare visual and spectrophotometric MICs readings of azoles and amphotericin B against A. fumigatus sensu lato isolates. Eight hundred and forty-seven A. fumigatus sensu lato isolates (A. fumigatus sensu stricto [n=828] and cryptic species [n=19]) were tested against amphotericin B, itraconazole, voriconazole, posac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
2
5
1
Order By: Relevance
“…However, all five clinical isolates of Afu were resistant to CMN but susceptible to known antifungals 5-FC (MIC = 3–12 μg/mL) and AmB (MIC = 180 ng/mL). The MICs for Afu were in line with the published MICs of 6 μg/mL for 5-FC and 0.2–1 μg/mL for AmB . Many fungal pathogens belong to Candida spp.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, all five clinical isolates of Afu were resistant to CMN but susceptible to known antifungals 5-FC (MIC = 3–12 μg/mL) and AmB (MIC = 180 ng/mL). The MICs for Afu were in line with the published MICs of 6 μg/mL for 5-FC and 0.2–1 μg/mL for AmB . Many fungal pathogens belong to Candida spp.…”
Section: Resultssupporting
confidence: 85%
“…The MICs for Af u were in line with the published MICs of 6 μg/mL for 5-FC 94 and 0.2−1 μg/mL for AmB. 95 Many fungal pathogens belong to Candida spp. and are major sources of hospital-acquired infections.…”
Section: ■ Resultsmentioning
confidence: 78%
“…An analysis of POS concentration monitoring in IPA treatment showed a strong clinical concentration-efficacy relationship ( 36 ). In this survey, the susceptibility rate of POS to intrapulmonary A. fumigatus isolates (18.9%; Table 1 ) was significantly different from that in a Spanish investigation (94 to 94.5%; P < 0.001) ( 20 ). However, the PK characteristics of POS ( Table 5 ) include the following: the protein affinity was 98%, the half-life was 24 to 27 h ( 37 ), the mean plasma C max was 3.2 μg/mL following administration of multiple doses of 400 mg twice daily ( 38 ), the ratio of penetration from plasma to ELF ranged from 0.20 to 0.31 in terms of total concentrations ( 39 ), and the mean value of the area under the concentration-time curve (AUC) from 0 to 12 h (AUC 0–12 ) in ELF ranged from 11.2 to 18.3 mg · h/L following oral administration of multiple doses of 400 mg twice daily in humans ( 40 , 41 ).…”
Section: Discussioncontrasting
confidence: 74%
“…In contrast, a high in vitro NS rate of AMB against clinical A. fumigatus isolates (80.2% of which exhibited MICs of ≥4 μg/mL) was found in Hamilton, Canada in 2015 ( 19 ). The present antifungal study also revealed significantly lower in vitro susceptibility rates of AMB against 660 pulmonary A. fumigatus isolates (49.5%; Table 1 ) and 22 VRC-resistant A. fumigatus isolates (45.5%; Table 1 ) compared to a 2019 Spanish study (98.5% against 847 clinical A. fumigatus sensu lato isolates; P < 0.001) ( 20 ) and a 2010 to 2016 Portugal study (84.7% against 190 clinical A. fumigatus isolates; P < 0.001) ( 21 ). There is a significant diversity in the susceptibilities of AMB to A. fumigatus isolates collected from different countries.…”
Section: Discussionsupporting
confidence: 41%
“…However, visual inspection may be challenging and the presence of tiny colonies may raise doubts about MIC interpretation. A recent study compared azole and amphotericin B MICs against A. fumigatus complex isolates obtained visually and spectrophotometrically (to overcome subjectivity) [32], showing high agreement between both methods, including for A. fumigatus sensu stricto isolates harbouring the dominant cyp51A gene mutation. The authors concluded that spectrophotometric MIC reading is a useful alternative to visual inspection and may become an option for determining MIC endpoints of azoles and amphotericin B in the near future.…”
Section: The Eucast Subcommittee On Antifungal Susceptibility Testing...mentioning
confidence: 99%